2018
DOI: 10.3390/ani8040054
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dietary Supplementation of Propolis and Bee Pollen on Liver Pathology in Broiler Chickens

Abstract: Simple SummaryToday, there are increased demands for consumers to use natural products as alternative additives in broiler feeding. In this study, we evaluated the effects of propolis and bee pollen as potential new additives on liver pathology in broilers. The results of this study showed that supplementation of broilers with propolis and/or bee pollen has a strong protective effect on liver pathology. Thus, these natural agents can be used as alternative additives in modern broiler production. Such an approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 22 publications
2
14
0
Order By: Relevance
“…Additionally, the hepatoprotective effects of these phytobiotics were suggested to be due to the presence of flavonoids in dandelion leaves and fenugreek seeds. Klaric et al’s [ 15 ] results also supported the results of the present study, where supplementation of phytobiotics such as propolis and bee pollen, which possess flavonoids, ameliorated the liver morphology compared to the control group. Additionally, normal hepatocytes without regressive lesions were noticed in the supplemented groups compared to the control.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Additionally, the hepatoprotective effects of these phytobiotics were suggested to be due to the presence of flavonoids in dandelion leaves and fenugreek seeds. Klaric et al’s [ 15 ] results also supported the results of the present study, where supplementation of phytobiotics such as propolis and bee pollen, which possess flavonoids, ameliorated the liver morphology compared to the control group. Additionally, normal hepatocytes without regressive lesions were noticed in the supplemented groups compared to the control.…”
Section: Discussionsupporting
confidence: 91%
“…Herbs have shown positive effects on the performance and biological health of broiler chickens [ 9 , 10 ], can improve haematological blood indicators and serum biochemical attributes [ 11 , 12 , 13 ], and have also been reported to regulate the kidney and liver functions [ 14 , 15 ]. Among such herbs, Persicaria odorata , of the family Polygonaceae, is of important significance.…”
Section: Introductionmentioning
confidence: 99%
“…The botanical source of the CBM propolis are P. davidiana dode and P. simonii Carr, they are common distributed in the mountains area of northeast China [31,32]. There are many research about possibilities of propolis usage in the medicine or veterinary medicine [33]. Further research regarding the biological activity of CBM propolis and its compounds is planned.…”
Section: Resultsmentioning
confidence: 99%
“…The present study revealed some original solutions regarding the applied dosage of investigated natural supplements and their specific combinations in broilers feeding, but was not without limitations. Due to the commonly accepted ’3Rs’, the authors had the justifiable wish to minimize the number of animals used in this study that had already been used in similar studies [3]. However, considering the tested natural feeding additives and main objective of this study, the authors believe that the described design of the study did not affect the results.…”
Section: Discussionmentioning
confidence: 99%
“…Propolis and bee pollen belong to a group of natural substances of animal and vegetable origin with intense antioxidant and antimicrobial properties [1]. The bioactive components of propolis and bee pollen include flavonoids, phenolic acids and their derivatives, which are also responsible for the bactericidal, antiviral, antifungal, analgesic, anti-inflammatory, antioxidant, immunostimulating and immunomodulating effects of these compounds in humans and animals [1,2,3].…”
Section: Introductionmentioning
confidence: 99%